ANALISIS MOTIVASI DALAM UPAYA MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN BAGIAN ADMINISTRASI PADA MITRA10 KOTA TANGERANG SELATAN - Lita Septiani; Melda Wiguna (Jurnal Menara, 2025)
This study aims to analyze the role of work motivation in increasing employee productivity in the administration department at Mitra10, South Tangerang City. This study used a qualitative method with a descriptive approach. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The research subjects consisted of seven administrative employees with different positions and length of service. The results showed that employee work motivation is influenced by various factors, including individual responsibility, achievement, self-development, and independence in work. Employees with high levels of motivation tend to show improvements in efficiency, effectiveness, and work quality. Conversely, decreased motivation occurs due to lack of training, minimal recognition for performance, suboptimal internal communication, and lack of involvement in decision-making. The use of new technology and the implementation of relevant training, particularly related to SOPs and administrative systems, has been shown to improve employee understanding and technical skills. Furthermore, the creation of a positive, collaborative work environment, supported by communicative and appreciative managerial leadership, can increase employee morale and loyalty. This study concludes that work motivation is a key factor in increasing work productivity in the administration department. Therefore, companies are advised to increase the effectiveness of training, improve communication and reward systems, and create a work atmosphere that supports the growth of employee professionalism.